2014
DOI: 10.1002/adma.201401554
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Nanoassembly Functions for an Effective Delivery Cascade for Cancer Drugs

Abstract: A "cluster-bomb"-like lipid-dendrimer nanoassembly synergizes the functions of its components and thereby efficiently accomplishes the drug delivery cascade for high efficacy in treating cancer. The nanoassembly successfully circulates in the blood and accumulates in the tumor. Once in the tumor, it releases small dendrimers that act like "bomblets", enabling tumor penetration, cell internalization, and drug release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
235
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 345 publications
(246 citation statements)
references
References 52 publications
4
235
0
7
Order By: Relevance
“…S16). These results substantiate previous observations that smaller nanoparticles are more advantageous for deep tumor penetration than larger ones because of their reduced diffusional hindrance (23,42). To further visualize real-time extravasation and tumor penetration of these nanoparticles, intravital CLSM was used.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…S16). These results substantiate previous observations that smaller nanoparticles are more advantageous for deep tumor penetration than larger ones because of their reduced diffusional hindrance (23,42). To further visualize real-time extravasation and tumor penetration of these nanoparticles, intravital CLSM was used.…”
Section: Resultssupporting
confidence: 66%
“…First, previous delivery systems simply focused on size-shrinkage medicated tumor penetration, whereas our system is devised to systematically overcome a series of barriers including tumor penetration. Achieving this goal is vitally important because these barriers are interconnected, and simply overcoming one individual barrier is not adequate to produce proper therapeutic outcomes (42,47). Second, the stimuli that were used to trigger size shrinkage previously were either by enzyme or UV light, whose applicability, to a certain extent, would be restricted to only a subset of cancer types owing to either the heterogeneous expression levels of target enzymes in a specific cancer type or the superficial penetration depth of UV light (14).…”
Section: Discussionmentioning
confidence: 99%
“…Motivated by our previous lipid-coated dendrimer nanoassembly [ 29 ] and multifunctional envelope-type nanodevice (MEND), [ 25 ] we hypothesized that while coating polyplexes with a PEGylated lipid layer would render them stealth properties, more importantly, the lipid layer might be engineered to fuse with the cell membrane and eject the polyplexes directly into the cytosol, mimicking the viropexis of a paramyxovirus, enabling the polyplexes to bypass the lysosomal pathway and thus avoid DNA degradation. Thus, a fusogenic lipid, 1,2-dioleoyl-sn -glycero-3-phosphoethanolamine (DOPE), and a PEGylated lipid 1,2-distearoyl-sn -glycero-3-phosphoethanolamine N -[methoxy(polyethylene glycol)-2000] (DSPE-PEG) were used as our previous report.…”
Section: Doi: 101002/adma201504288mentioning
confidence: 99%
“…Thus, a fusogenic lipid, 1,2-dioleoyl-sn -glycero-3-phosphoethanolamine (DOPE), and a PEGylated lipid 1,2-distearoyl-sn -glycero-3-phosphoethanolamine N -[methoxy(polyethylene glycol)-2000] (DSPE-PEG) were used as our previous report. [ 29 ] A negatively charged fusogenic lipid, cholesteryl hemisuccinate (CHEMS), was used as a helper lipid to bind the positively charged polyplex to make the surface hydrophobic for DOPE and DSPE-PEG coating. The lipid ratios were fi ne-tuned and found that at a DOPE/CHEMS/ DSPE-PEG ratio of 7.65/2/1.35, where DSPE-PEG was 15% of total lipid, hydration of the polyplexes ( N / P of 13) with the lipid fi lm formed spherical FLPPs of around 120 nm in diameter with a zeta potential of −6 mV ( Figure 4 a and Figure S15a, Supporting Information).…”
Section: Doi: 101002/adma201504288mentioning
confidence: 99%
“…As such, a nanocarrier achieves high delivery and therapeutic efficacy only if it efficiently meets all conditions of the CAIR theory. 30 Therefore, to develop PEI-based nanocarriers in view of the CAIR theory, multiple elements should be modified in the skeleton material (Scheme 1): in blood circulation, polyethylene glycolation (PEGylation) can be used to make nanocarriers able to escape extracellular nucleases, evade the reticuloendothelial system, and avoid aspecific interaction with blood cells; [31][32][33][34] to increase accumulation at tumor sites, suitable particle sizes are necessary 30 (nanocarriers around 100 nm have longer blood-circulation times and better tumor accumulation than smaller particles); and cell-penetrating peptides, which can improve translocation across the plasma membrane and increase intracellular drug concentration, are often used to increase internalization of payloads by tumor cells. is known to facilitate and enhance cellular internalization efficiently in a large variety of electrostatically or covalently bound cargoes in a nontoxic fashion.…”
Section: Introductionmentioning
confidence: 99%